A holistic approach to sustainable energy development at regional level: The RENERGY self-assessment methodology. (September 2015) - Cosmi, Carmelina; Dvarionenė, Jolanta; Marques, Isabel; Di Leo, Senatro; Gecevičius, Giedrius; Gurauskienė, Inga; Mendes, Gisela; Selada, Catarina
Abstract: The energy challenge is a complex issue that EU is facing. A sustainable, safe and competitive energy supply and climate change mitigation are nowadays key priorities of EU energy policy and a need for each EU Member State. Sustainable energy development at the regional level is a multiple and complex activity, involving various stakeholders and different measures. Three main thematic pillars, policy making, energy market and community involvement, have been identified as crucial in order to implement effective and feasible policy and measures at the regional scale. In this framework, the initial assessment of regional energy systems is an essential step to set up customized sustainable energy strategies. In the framework of the INTERREG IVC RENERGY project a structured methodology for the initial assessment of local communities (Self-Assessment -SAA) was defined and applied to the analysis of the partners' communities located in nine European Countries (Lithuania, Denmark, Italy, Portugal, United Kingdom, Germany, Austria, Hungary and Romania) in order to outline the status of local energy infrastructures, renewable and energy efficiency potentials and to highlight the key issues to be exploited in the local implementation plans. The holistic approach of the SAA methodology is aimed at characterising the energy systems in terms of policy background, energy uses and infrastructures as well as market behaviour and community attitude for sustainable development, valorising the interrelationships among the project thematic pillars.